2010
DOI: 10.1161/circresaha.109.215483
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Promotes Proliferation and Prevents Senescence Through Targeting LKB1 in Primary Porcine Aortic Endothelial Cells

Abstract: Under conditions that cause endothelium injury, such as hypertension, high cholesterol levels and turbulent blood flow, replication of endothelial cells is increased for regenerating the damaged endothelium. 3 However, the regenerated endothelial cells usually reach replicative senescence after a finite number of cell replication. Senescent endothelial cells show diminished vasomotor-regulatory activities and elevated expression of proinflammatory molecules, which contribute to the development of age-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
222
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(233 citation statements)
references
References 43 publications
8
222
2
1
Order By: Relevance
“…The finding that SIRT1 overexpression improves iPSC-EC performance in our investigation agrees with studies by others on primary ECs, which may provide a mechanistic insight to our findings [14,21,22]. A previous study concluded that SIRT1 influences EC proliferation and prevents senescence by promoting the deacetylation, ubiquitination, and proteasome-mediated degradation of LKB1, a serine/ threonine kinase and tumor suppressor [14].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The finding that SIRT1 overexpression improves iPSC-EC performance in our investigation agrees with studies by others on primary ECs, which may provide a mechanistic insight to our findings [14,21,22]. A previous study concluded that SIRT1 influences EC proliferation and prevents senescence by promoting the deacetylation, ubiquitination, and proteasome-mediated degradation of LKB1, a serine/ threonine kinase and tumor suppressor [14].…”
Section: Discussionsupporting
confidence: 92%
“…A previous study concluded that SIRT1 influences EC proliferation and prevents senescence by promoting the deacetylation, ubiquitination, and proteasome-mediated degradation of LKB1, a serine/ threonine kinase and tumor suppressor [14]. In another study, inhibition of SIRT1 activity in ECs resulted in a premature senescent-like phenotype through an increased p53 acetylation in parallel with an increased plasminogen activator inhibitor-1 (PAI-1) expression and decreased eNOS expression [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the important substrates deacetylated by SIRT1 in endothelial cells (ECs) are eNOS (Mattagajasingh et al 2007), LKB1 (Zu et al 2010), Notch (Guarani et al 2011), and p66shc . The net effect of SIRT1 in ECs appears to be control of vessel growth (Potente et al 2007) and protection against EC senescence (Ota et al 2007) and, more generally, atherosclerosis.…”
Section: Endothelium and Smooth Musclementioning
confidence: 99%
“…Moreover, SIRT1 safeguards ECs from senescence by preventing prolonged LKB1 AMPK signaling through LKB1 deacetylation and degradation. 90 Interestingly, AMPK enhances SIRT1 activity by elevating NAD ϩ levels, 91,92 suggesting that LKB1 AMPK and SIRT1 engage in a negative feedback loop that prevents sustained LKB1 AMPK activation ( Figure 5). Recent studies also illustrated that SIRT1 suppresses the expression of p66SHC, an adaptor protein whose inactivation protects mice from agingassociated vascular disease.…”
Section: Endothelial Aging Phenotypes Are Regulated By Sirtuins and Fmentioning
confidence: 99%